Pensamento algébrico: quais elementos são identificados por professores de Matemática em atividades com este foco? - Soares, Renata Mendes (2018)
Our investigation, which has a qualitative character, has as goal to indicate which aspects related to the development of algebraic thinking are identified by four Mathematic teachers that operate on the second cycle of elementary School in a São Paulo’s public school. For that purpose, Blanton and Kaput; Kieran; Fiorentini, Miorin and Miguel; Fiorentini, Fernandes and Cristóvão; Ponte, Branco and Matos and Blanton were adopted as reference and guided each moment of our research. Initially we proposed to the participants the resolution of three activities that presented an algebraic nature and were destined to the sixth and seventh grades of elementary school, as well as some questions regarding the Algebraic thinking and Algebra teaching. We have done, also, a presentation to the participants about the research’s themes. At last, teachers were interviewed with the intent of clarifying points of their written production or participation on the moment of the presentation, which demanded further explanations. After the analysis of the written production and audio tapes, made during the presentation and interviews, we verified that the participants identified some elements characterizing a work that prioritizes the development of the algebraic thought, as we hoped. Elements such as equivalency of numeric expressions and algebraic; not obligatory use of an algebraic language to resolution of problems; use of different representations; comprehension of the structure of a calculation. However, none of them identified the generalization, element that we hoped they would indicate. This element is already present on three activities chosen as our instrument of data collection